2023
DOI: 10.1037/ocp0000338
|View full text |Cite
|
Sign up to set email alerts
|

When does exposure to daily negative acts frustrate employees’ psychological needs? A within-person approach.

Abstract: Based on self-determination theory, this two-sample study investigates the effects of negative acts on psychological need frustration in greater depth using a within-person perspective. More specifically, through two distinct diary studies, we aim to contribute to the dearth of research on the daily effects of bullying by investigating the daily relationship between exposure to negative acts and need frustration as well as the moderating role of perceived emotional support at work in this relationship. Overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…Interestingly, they also found that the trajectory of anxiety and depressive symptoms experienced by the participants across the same period was very similar to the evolution of exposure to bullying behaviors, suggesting that the symptoms could reflect a short-term response to the negative acts. In a similar vein, very recently, Trépanier et al (2023) documented a relationship between being subjected to daily bullying behaviors and psychological need frustration as indicated, for example, by perceived rejection and oppression.…”
mentioning
confidence: 85%
“…Interestingly, they also found that the trajectory of anxiety and depressive symptoms experienced by the participants across the same period was very similar to the evolution of exposure to bullying behaviors, suggesting that the symptoms could reflect a short-term response to the negative acts. In a similar vein, very recently, Trépanier et al (2023) documented a relationship between being subjected to daily bullying behaviors and psychological need frustration as indicated, for example, by perceived rejection and oppression.…”
mentioning
confidence: 85%
“…Second, as research shows that shorter, rather than longer, time frames best tap into the longitudinal impact of contextual factors (Lesener, Gusy & Wolter, 2019), the time lag utilized in the present study (i.e., a 3month period between measurement points) may have been too long to capture the buffering effect of coworker support in the longitudinal relationship between tyrannical leadership and exposure to negative behaviors. Given that coworker emotional support has been found to buffer the daily relationship between exposure to negative acts and need frustration (Tr epanier, Peterson, M enard & Notelaers, 2023), future diary studies are encouraged to capture the short-term dynamics between tyrannical leadership, coworker support, and exposure to bullying behaviors.…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…Bullying can also happen in a direct or indirect way. Indirect bullying is subtler and includes disregarding, nattering, and undermining behaviors whereas direct bullying comprehends apparent, unconcealed behavior such as terrorization, disparagements, and degradation (Trépanier et al, 2022). Workplace bullying creates continual and insistent destructive activities pointed at one or more persons which result in the formation of an unfriendly working situation.…”
Section: Introductionmentioning
confidence: 99%